MENINGKATKAN HASIL BELAJAR PAI DENGAN MENERAPKAN STRATEGI THINK-TALK-WRITE DALAM KELOMPOK KECIL DI SMA NEGERI 1 KOTO GASIB - Abdul Rokhim (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2020)
This study aims to determine the increase in the ability of teachers to apply innovative learning with the Think-Talk-Write strategy in small groups as an alternative to improving the learning outcomes of Islamic Education in the material of Rasul-Rasul that is the Lover of Allah SWT. Think-Talk-Write (TTW) is a learning model developed by Huinker and Laughlin. In this learning model, students are encouraged to think, talk, and then write about a topic. This action research was conducted at SMA Negeri 1 Koto Gasib in Class XI, with 29 students consisting of 27 Muslim students and 2 non-Muslim students. This research took place in Semester Two of the 2018/2019 Academic Year. The data collection technique of this research was observation, distributing questionnaires and daily tests / tests. From the learning activities with the Think-Talk-Write strategy in small groups that have been conducted in this study, it can be seen that there has been an increase in learning outcomes. Therefore, this learning approach is very suitable in class to help students enlarge their knowledge.